Environmental Interventions to Reduce the Consumption of Sugar-Sweetened Beverages: Abridged Cochrane Systematic Review - von Philipsborn, Peter (Obes Facts, 2020)
BACKGROUND: Regular consumption of sugar-sweetened beverages (SSB) can increase the risk for obesity, type 2 diabetes, cardiovascular disease, and dental caries. Interventions that alter the physical or social environment in which individuals make beverage choices have been proposed to reduce the consumption of SSB. METHODS: We included randomised controlled, non-randomised controlled, and interrupted time series studies on environmental interventions, with or without behavioural co-interventions, implemented in real-world settings, lasting at least 12 weeks, and including at least 40 individuals. Studies on the taxation of SSB were not included, as these are subject of a separate Cochrane review. We used standard Cochrane methods for data extraction, risk of bias assessment, and evidence grading and synthesis. Searches were updated to January 24, 2018. RESULTS: We identified 14,488 unique records and assessed 1,030 full texts for eligibility. We included 58 studies comprising a total of 1,180,096 participants and a median length of follow-up of 10 months. We found moderate-certainty evidence for consistent associations with decreases in SSB consumption or sales for the following interventions: traffic light labelling, price increases on SSB, in-store promotion of healthier beverages in supermarkets, government food benefit programs with incentives for purchasing fruits and vegetables and restrictions on SSB purchases, multi-component community campaigns focused on SSB, and interventions improving the availability of low-calorie beverages in the home environment. For the remaining interventions we found low- to very-low-certainty evidence for associations showing varying degrees of consistency. CONCLUSIONS: With observed benefits outweighing observed harms, we suggest that environmental interventions to reduce the consumption of SSB be considered as part of a wider set of measures to improve population-level nutrition. Implementation should be accompanied by evaluations using appropriate methods. Future studies should examine population-level effects of interventions suitable for large-scale implementation, and interventions and settings not yet studied thoroughly.